Hygroscopic Porous Polymer for Sorption‐Based Atmospheric Water Harvesting - Fangfang Deng; Zhihui Chen; Chenxi Wang; Chengjie Xiang; Primož Poredoš; Ruzhu Wang (Advanced Science, 2022)
Abstract Sorption‐based atmospheric water harvesting (SAWH) holds huge potential due to its freshwater capabilities for alleviating water scarcity stress. The two essential parts, sorbent material and system structure, dominate the water sorption–desorption performance and the total water productivity for SAWH system together. Attributed to the superiorities in aspects of sorption–desorption performance, scalability, and compatibility in practical SAWH devices, hygroscopic porous polymers (HPPs) as next‐generation sorbents are recently going through a vast surge. However, as HPPs’ sorption mechanism, performance, and applied potential lack comprehensive and accurate guidelines, SAWH's subsequent development is restricted. To address the aforementioned problems, this review introduces HPPs’ recent development related to mechanism, performance, and application. Furthermore, corresponding optimized strategies for both HPP‐based sorbent bed and coupling structural design are proposed. Finally, original research routes are directed to develop next‐generation HPP‐based SAWH systems. The presented guidelines and insights can influence and inspire the future development of SAWH technology, further achieving SAWH's practical applications.